Overview of Adolescent Girls' Knowledge regarding Anemia Prevention at SMKN 2 Denpasar - Yanti, Ni Luh Putu Risma; Somoyani, Ni Ketut; Tedjasulaksana, Regina; Parmiati, Ni Komang Wiary (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Adolescent girls are a high-risk group for anemia due to physiological changes, particularly menstruation, as well as behavioral and nutritional factors. Inadequate knowledge regarding anemia prevention may increase this risk. This study aimed to describe the level of knowledge among adolescent girls regarding anemia prevention at SMK Negeri 2 Denpasar. A descriptive research design with a cross-sectional approach was employed. Data were collected using structured questionnaires administered to 65 tenth-grade female students selected through purposive sampling from a total population of 118 students. The study was conducted on May 22, 2025. Knowledge levels were categorized into good (80–100), sufficient (60–79), and poor (<60) based on respondents’ scores. The results showed that most respondents were 16 years old (64.6%), predominantly from the accounting major (67.7%), and 60% had previously received education about anemia. Electronic media was identified as the primary source of information (46.2%), followed by interpersonal sources such as family and peers (30.8%), and print media (23.1%). Overall, the majority of respondents (60%) demonstrated a good level of knowledge regarding anemia prevention, while a smaller proportion had sufficient (32.3%) and poor knowledge (7.7%). Despite generally favorable knowledge levels, gaps remain in specific aspects of anemia prevention, particularly related to menstrual health and comprehensive prevention strategies. Therefore, more structured, continuous, and context-based health education interventions are needed, involving both schools and healthcare professionals, to enhance adolescents’ understanding and promote effective anemia prevention behaviors.